Reducing Student Nurse Stigmatization of the Patient Who Misuses Opioids A Scoping Review - Maynard, Kristi (Journal of Addictions Nursing, 2020)
The United States is in the midst of an opioid epidemic. The numbers of opioid-related deaths have been steadily climbing, magnifying the need for innovative intervention. Stigma is a set of preconceived, negative assumptions about a patient population or group. Stigma is a known deterrent to communication and the delivery of healthcare. Nurses serve as a primary contact for many marginalized patients within the healthcare system. The purpose of this scoping review is to gather known data on the use of educational interventions with nursing students to reduce stigmatizing tendencies. Inclusion criteria constituted an educational intervention involving student nurses and an effort to reduce stigmatizing attitudes toward patients who misuse opioids. The intervention must have taken place in an institute of higher learning between the years of 2003 and 2018. Exclusion criteria included community-wide studies. A single study was identified addressing nursing student reduction of stigmatization of the individual who uses opioids, and so, the search was expanded to include any student nursing intervention developed to reduce stigma toward any marginalized population. The following electronic databases were utilized in the search process: Cumulative Index of Nursing and Allied Health Literature, Google Scholar, Journal Storage, Microsoft Academic, and ScienceDirect. Reference pages of selected or related articles were reviewed in an attempt to identify additional pertinent literature through citation mapping. Fifteen studies were identified, each of which utilized a variable methodology for stigma reduction with varying levels of success. © Lippincott Williams & Wilkins.
3 citations (Crossref) [2023-10-31] WOS:000526707500008
Keywords: Attitude of Health Personnel; Clinical Competence; Humans; Opioid-Related Disorders; Social Stigma; Stereotyping; Students; Nursing; clinical competence; dept.nur; education; health personnel attitude; human; nurse; nursing student; opiate addiction; opioid misuse; peer-reviewed; psychology; social stigma; stereotyping; stigma; student